Money Demand in the Netherlands - Traa, Bob (IMF Working Papers; Working Paper ;, 1991)
This paper analyzes the demand for narrow money balances in the Netherlands. Demand for narrow money balances had increased markedly in relation to GNP in the Netherlands throughout the 1980s. This phenomenon could not be explained satisfactorily with traditional Goldfeld-type money demand functions which had performed well until that time. Drawing on advances in dynamic modeling from the error corrections and cointegration literature, and incorporating yield-curve effects and the exchange rate of the guilder with the U.S. dollar as additional monetary indicators significantly improves the performance of money demand estimates.